Respiratory muscular strength decrease in children with mylomeningocele - Ronchi, Carlos Fernando [UNESP]; de Oliveira Antunes, Leticia Claudia [UNESP]; Fioretto, José Roberto [UNESP] (Lippincott Williams & Wilkins, 2008)
Study Design. Case-control study.Objective. To evaluate respiratory muscle force in children with myelomeningocele. Summary of Background Data. Myelomeningocele is a common spinal cord malformation with limitations linked to central nervous system lesions and abnormalities in respiratory movements. Despite this, little attention has been given to evaluating respiratory muscle force in these patients.Methods. Children with myelomeningocele aged between 4 and 14 years ( myelomeningocele group; MG, n = 20) were studied and compared with healthy children ( control group; CG, n = 20) matched for age and gender. Respiratory muscular force was evaluated by maximum inspiratory ( Pimax) and expiratory ( Pemax) pressures.Results. Groups were similar for age [ CG = 8 ( 6 - 13) = MG = 8 ( 4 - 14), P > 0.05]; gender, and body mass index [ CG = 17.4 ( 14.1 - 24.7) x MG = 19.2 ( 12.6 - 31.9), P > 0.05]. The lumbosacral region was predominantly affected ( 45%). Maximum respiratory pressures were significantly higher in CG than MG ( Pimax = CG: similar to 83 +/- 21.75 > MG: -54.1 +/- 23.66; P < 0.001 and Pemax = CG: + 87.4 +/- 26.28 > MG: + 64.6 +/- 26.97; P = 0.01). Patients with upper spinal lesion ( UL) had lower maximum respiratory pressure values than those with lower spinal lesion ( LL), [Pimax ( UL = - 38.33 +/- 11.20 cm H2O x LL = - 60.85 +/- 24.62 cm H2O), P < 0.041 and Pemax ( UL = + 48 +/- 20.82 cm H2O x LL + 71.71 +/- 26.73 cm H2O), P = 0.067]).Conclusion. Children with myelomeningocele at the ages studied presented reduced respiratory muscle force with more compromise in upper spinal lesion.
Keywords: respiratory muscle; myelomeningocele; children; spina bifida; maximal respiratory pressure